A miR-JL-5 inhibitor modulates the proliferation of Nosema ceranae in Apis cerana - Han, Xu; Xiao, Jin Hua; Yan, Wei Yu; He, Xu Jiang; Zeng, Zhi Jiang (Frontiers in Insect Science, 2025)
Background and aimsApis cerana is the native host of Nosema ceranae (N. ceranae). Previous studies reported that N. ceranae was more harmful to the new host (Apis mellifera) than the original host that had spread globally and become one of the factors implicated in honeybee colony collapses. Therefore, it was essential to study the relationship between Apis cerana and N. ceranae for the prevention and control of the disease.MethodsIn order to effectively block the regulation of spore proliferation in honeybees, we designed a miR-JL-5 inhibitor. In this study, infected bees (Apis cerana) were fed sugar water with N. ceranae miR-JL-5 inhibitor in incubators using RNA interference technology. The spores load and the expression of microRNA, DEmRNA, and target gene among miRNA inhibitor group, infection group, and miRNA scramble group were compared. Both the biological functions of miR-JL-5 and the target gene of miRNAJL-5, were verified using RNA interference.ResultsOur results showed that expression levels of JL-5 and the spore load in the miRNA inhibitor group were significantly lower than those in the infection and miRNA-scramble groups. We predicted that 847 honeybee genes and 133 N. ceranae genes can be targeted by the miR-JL-5. Whole transcriptome sequencing results showed that a total of 5 honeybee DEmRNAs, and 0 N. ceranae DEmRNA were identified in miRNA inhibitor group, infection group, and miRNA scramble group, in which only the honeybee mucin-19-like gene was the target gene by miR-JL-5.ConclusionThese findings reveal that feeding miR-JL-5 inhibitor could reduce N. ceranae levels by altering the expression of miR-JL-5 and related target gene (honeybee mucin-19-like gene). Our results provide insights into role that microRNA regulates the proliferation of N. ceranae in Apis cerana.